Organizational factors, individual factors, perceived organizational support and perceived public recognition on unethical behavior among police personnel / Nusrah Samat - Samat, Nusrah (2016)
Ethics has been an issue of enormous interest and growing concern from time to time in most areas including in the management field. The inculcation of unethical behavior in both public and private organizations has proven to be an elusive and never ending quest. The issue of unethical conduct is also evident in Malaysia. This can be seen by the increasing frequency of coverage in media, printing and electronic, on unethical behavior and misconducts by individuals and local organizations. Unethical behaviors lead to a wide range of negative consequences. The costs associated with unethical behavior in the organization are great, estimated to be in the amount of billions annually as well as it may negatively impact the organizations’ ability to achieve sustained profitability.